Self-Directed Learning, Academic Achievement and Motivation: A Meta-Analytical Study - Yurdal, Mustafa Onur; Toraman, Çetin (Alberta Journal of Educational Research, 2023)
This study is a meta-analytical examination of the relationships between academic achievement, motivation, and self-directed learning. It aims to review scientific studies investigating how self-directed learning readiness relates to both motivation and academic achievement to find a common effect level and to synthesize the study results. According to the meta-analytical results, it can be seen that academic achievement increases in line with an increase in the level of self-directed learning readiness. The results reveal that the relationship between self-directed learning and both motivation and academic achievement, which are two important indicators of the educational process, constitutes an important structure. It is recommended that relational studies conducted at the K–12 level of the relationship between self-directed learning and motivation should be compared with the results of this study through a separate meta-analysis. Keywords: self-directed learning, academic achievement, motivation, lifelong learning, meta-analysis Cette étude est un examen méta-analytique des relations entre les résultats scolaires, la motivation et l'apprentissage autodirigé. Elle vise à passer en revue les études scientifiques portant sur la manière dont la préparation à l'apprentissage autodirigé est liée à la fois à la motivation et aux résultats scolaires, afin de trouver un niveau d'effet commun et de synthétiser les résultats de l'étude. Les résultats de la méta-analyse montrent que les résultats scolaires augmentent en fonction du niveau de préparation à l'apprentissage autodirigé. Les résultats révèlent que la relation entre l'apprentissage autodirigé et la motivation et les résultats scolaires, qui sont deux indicateurs importants du processus éducatif, constitue une structure importante. Il est recommandé que les études relationnelles menées au niveau M à 12 sur la relation entre l'apprentissage autodirigé et la motivation soient comparées aux résultats de cette étude par le biais d'une méta-analyse séparée. Mots clés : apprentissage autodirigé, résultats scolaires, motivation, apprentissage tout au long de la vie, méta-analyse